2012
DOI: 10.1111/j.1365-2036.2012.05188.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: pre‐dosing with taribavirin before starting pegylated interferon vs. standard combination regimen in treatment‐naïve patients with chronic hepatitis C genotype 1

Abstract: SummaryBackgroundCombination therapy with the ribavirin (RBV) prodrug taribavirin (TBV) and pegylated interferon (PIFN) has produced lower rates of anaemia than with RBV and PIFN. Studies have demonstrated that the sharpest decline in viral load during TBV therapy occurs at Weeks 4 through 6, when TBV reaches steady-state blood levels.AimThe current proof-of-concept study was conducted to examine whether first-order viral kinetics could be influenced by pre-dosing TBV to steady state before introducing PIFN.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…These results could reflect a greater susceptibility of HCV to pegIFN following pre‐dosing with RBV, and thus enhanced effectiveness. In a recent study [Palmer et al, ], 42 chronic hepatitis C‐1 naïve patients were randomised to receive treatment either with four weeks of taribavirin in monotherapy, followed by combined treatment with pegIFN, or the combined treatment directly. Palmer et al [] also observed greater reductions in HCV‐RNA levels during the treatment, and suggested that pre‐dosing with taribavirin prior to starting pegIFN improves efficacy, although statistical significance was not achieved in this small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results could reflect a greater susceptibility of HCV to pegIFN following pre‐dosing with RBV, and thus enhanced effectiveness. In a recent study [Palmer et al, ], 42 chronic hepatitis C‐1 naïve patients were randomised to receive treatment either with four weeks of taribavirin in monotherapy, followed by combined treatment with pegIFN, or the combined treatment directly. Palmer et al [] also observed greater reductions in HCV‐RNA levels during the treatment, and suggested that pre‐dosing with taribavirin prior to starting pegIFN improves efficacy, although statistical significance was not achieved in this small number of patients.…”
Section: Discussionmentioning
confidence: 99%